Pengaruh Dukungan Keluarga terhadap Kualitas Tidur Ibu - Siska Febrina Fauziah (JURNAL PENDIDIKAN KESEHATAN, 2024)
Poor sleep quality is the most common complaint reported by women during the postpartum period. Inadequate and disrupted sleep after childbirth is strongly associated with postpartum depression, and vice versa. Sleep difficulties during this period may not be fully resolved until six years after the baby is born. This study aimed to determine the impact of family support, including assistance with baby care and household chores, on mothers' sleep quality. The research was conducted using a cross-sectional method with the standardized Pittsburgh Sleep Quality Index (PSQI) questionnaire administered online. The respondents were 214 mothers with children aged 0–2 years. The study results revealed that 70.1% of respondents received assistance with baby care, and 56.1% received help with household chores, either from their husbands, family members, childcare services, or domestic helpers. However, approximately 79% of respondents still experienced poor sleep quality. Chi-square test results showed a p-value > 0.05, indicating no significant effect of family support in baby care and household chores on mothers' sleep quality. It is crucial for healthcare professionals to educate families about the importance of mothers' rest needs to prevent sleep disturbances from impacting the health of both the mother and the family.